1995
DOI: 10.1001/archinte.155.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Is postmenopausal estrogen therapy associated with neuromuscular function or falling in elderly women? Study of Osteoporotic Fractures Research Group

Abstract: We found no evidence that postmenopausal estrogen use has beneficial effects on muscle strength or neuromuscular function or that it reduces the risk of falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…In agreement with the findings of a large observation study, The Study of Osteoporotic Fractures, we found that postmenopausal HT use did not significantly reduce the risk of falling 28. HT was associated with a non-significant risk reduction in both falls and fractures between years 3 and 6.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the findings of a large observation study, The Study of Osteoporotic Fractures, we found that postmenopausal HT use did not significantly reduce the risk of falling 28. HT was associated with a non-significant risk reduction in both falls and fractures between years 3 and 6.…”
Section: Discussionsupporting
confidence: 90%
“…Substantial improvements in postural balance after later initiation of HT seem to be more doubtful, and significant effects have not been observed in women older than 69 and 65 years of age in other studies. 35,36 Additional prospective studies are required to examine whether HT can improve postural balance when initiated in older women and, if improvements are possible, to find the relevant therapeutic dose range and optimal duration of therapy to substantially improve postural balance.…”
Section: Discussionmentioning
confidence: 99%
“…The same protocol for measuring grip strength was used at the follow-up visit. Previous studies have shown a high reproducibility of grip strength in older adults [19][20][21]. Change in grip strength (baseline -follow-up) was calculated as absolute values as well as percent change during follow-up.…”
Section: Methodsmentioning
confidence: 99%